2018
DOI: 10.1007/s40263-018-0515-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cannabinoid Type 2 Receptor by a Novel Indazole Derivative Normalizes the Survival Pattern of Lymphoblasts from Patients with Late-Onset Alzheimer’s Disease

Abstract: Our results suggest that the activation of CB2 receptors could be considered a useful therapeutic approach for Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…During the last decade, an accumulated body of evidence demonstrated that targeting CB2 receptors might serve as a promising therapeutic approach for Alzheimer's and other neurodegenerative diseases, as they are present in dendritic cells, neuronal cells, and microglia . Furthermore, the stimulation of CB2 receptors is generally known to have an anti‐inflammatory effect or may enhance tissue damage in some conditions .…”
Section: Future Directions For Alzheimer's Disease Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, an accumulated body of evidence demonstrated that targeting CB2 receptors might serve as a promising therapeutic approach for Alzheimer's and other neurodegenerative diseases, as they are present in dendritic cells, neuronal cells, and microglia . Furthermore, the stimulation of CB2 receptors is generally known to have an anti‐inflammatory effect or may enhance tissue damage in some conditions .…”
Section: Future Directions For Alzheimer's Disease Treatmentmentioning
confidence: 99%
“…167 During the last decade, an accumulated body of evidence demonstrated that targeting CB2 receptors might serve as a promising therapeutic approach for Alzheimer's and other neurodegenerative diseases, as they are present in dendritic cells, neuronal cells, and microglia. 168 Furthermore, the stimulation of CB2 receptors is generally known to have an anti-inflammatory effect or may enhance tissue damage in some conditions. 169 It should be mentioned that the expression levels of CB2 receptors are dictated by Aβ42 levels and plaque accumulation, suggesting the stimulation of CB2 receptor expression by these pathogenic events.…”
Section: Cannabinoid Type 2 Receptor Agonistsmentioning
confidence: 99%
“…Experiments utilizing the MWM and NOR tests [46,47,49,51] supported this correlation. Notably, a decrease in pro-inflammatory cytokines such as TNF-a, IL-1β and COX-2, and apoptotic enzymes such as caspase-3, was observed [47,51], further supported by [48], who found that PGN33 reduced the death rate of Aβ-challenged neuroblastoma cells. These findings suggest that CB2R agonists possess anti-inflammatory and immunomodulatory properties possibly via suppression of the TLR4/NF-κB p65 pathway [49].…”
Section: Discussionmentioning
confidence: 61%
“…Del Cerro et al [48] demonstrated the effectiveness of the innovative CB2R agonist, PGN33 (Scheme 2), in influencing the viability of lymphoblasts isolated from late-onset AD patients. PGN33 administration at varying doses (2.5nM, 5nM, 7.5nM, 10nM) dose-dependently decreased the viability of NA-lymphoblasts, limiting their uncontrolled proliferation with a potency similar to that of the agonist JWH-133.…”
Section: Selective Agonists Of Cannabinoid Receptor 2 (Cb2r)mentioning
confidence: 99%
“…These human cell lines arise from peripheral B lymphocytes infected in vitro with the Epstein–Barr virus; a process that immortalizes them [29]. Some studies have already shown alterations in the cell cycle, proliferative activity and Aβ processing, as well as higher oxidative stress in AD than control-derived LCLs [30,31,32,33,34,35,36,37,38,39].…”
Section: Introductionmentioning
confidence: 99%